The Decomposition Pathways of C₄F₇N/CO₂ Mixtures in the Presence of Organic Insulator Vapors - Sijie Liu; Xiaolong Li; Wen Wang; Zhenxin Geng; Ying Lin (IEEE Access)
As a potential substitute for SF6, C4F7N/CO2 mixture gas has a broad application prospect in gas insulated substation (GIS) busbars and high-voltage circuit breakers. Under high temperature conditions, Polytetrafluoroethylene (PTFE) vapor may have a significant effect on the decomposition path of C4F7N/CO2 mixture, which has far-reaching significance for the study of arc extinction characteristics. The decomposition mechanism of C4F7N/CO2 mixture in PTFE vapor environment was investigated by using density functional theory (DFT) for quantum chemical calculation. In this study, the structure and vibration frequency of the optimized intermediates were calculated accurately, and the energy of the reactants and intermediates was evaluated by G4 theory method. The decomposition path of C4F7N/CO2 mixture under the influence of PTFE vapor was revealed by analyzing the decomposition path potential energy. This paper not only provides a theoretical basis for the interaction between PTFE vapor and C4F7N/CO2 mixture, but also provides a reference for the study of arc extinguishing characteristics of environmentally friendly gases in high voltage circuit breakers.